Religious coping among wives whose husband had extramarital affairs - Makarim, Zahira Rahmatika; Filsuf T, Muhammad Novvaliant (Jurnal Psikologi Islam, 2017)
This study aims to explore the dynamic of religious coping on the wives whose husband had extramarital affair. Religious coping is also taught by Islam. Every muslim is commanded to be patient in dealing with every problem. This verse is commanded ery problem. This command is genai orang tua. ng menyin Al-Qur’an surah Al-baqarah:155 that said “we test you with danger, hungry and losing something that precious to you like life and fruits; then give good news for them who always patient”. Respondents in this research are two wives as victims of extramarital affair by their husbands. They engaged in religious coping to cope with their situation. Researcher use qualitative method with phenomenology design. Data were collected by interview. The content of the interview guideline constructed based on Pargament’s questionnare of religious coping. The data was classifying into categories and sub-categories. The result showed that using negative religious coping in respondent N withdrawn her from God and caused her to focus on negative emotion. Meanwhile, using positive religious coping in respondent N and F created positive emotion where both respondent succeed to conquer and take benevolent from the problem. In conclusion, religious coping (especially positive religious coping) helps respondents to have control over theirselves. Before the used of this coping, respondents tend to used emotion focus to control their feeling then manifested in negative behavior. Religiousity need to be developed by doing more religious activities to increase positive religious coping. In the other hand, respondents have to learn forgiving and stop blaming theirselves which might make them involved more in their negative emotion. Key words : Extramarital affair , Religious coping